Protecting Children from Cybercrime : Legislative Responses in Asia to Fight Child Pornography, Online Grooming, and Cyberbullying - Song, Janice Kim (World Bank, Washington, DC; International Centre for Missing & Exploited Children, Alexandria, Virginia, 2015)
Information and communication technologies (ICTs) have developed rapidly over the last two decades. The development of ICTs have allowed adults, as well as children, to enjoy unprecedented opportunities and benefits in terms of socialization, education, and entertainment. On the other hand, recent rapid advances in ICTs simultaneously have allowed violence to be committed by, with, and through the use of ICTs, including violence against children. Accordingly, children using the Internet and associated technologies become vulnerable to ICT-facilitated child abuse and exploitation and such child abuse and exploitation are often difficult to detect and address. In response to a growing concern over the use of ICTs to commit violence against children, an Asian regional study on legislative responses for the protection of children from violence through ICTs was conducted. This regional study provides an overview of 17 targeted Asian countries' legislative responses to online child abuse and exploitation, with a particular focus on activities related to child pornography (also known as "child abuse images"), online grooming, and cyberbullying. This regional study pays special attention to: 1) analyzing legislative measures to address violence against children committed by, with, and through the use of ICTs in alignment with relevant international instruments; 2) presenting examples of good practice in a legal enabling environment for child online protection at a national level in compliance with relevant international standards; and 3) highlighting recommendations for strengthening the national legal framework to handle ICT-facilitated child abuse and exploitation amongst the 17 Asian countries analyzed.